New Dimensions in Reclamation: Indianapolis, Indiana - Vance Rzepka; Ted Spaid (Oz, 1985)
Continuous population increases are causing United States cities to grow much faster than their respective land areas will allow. As each city limit gradually expands, distinction between one city and another becomes unclear, thus creating a situation known as 'lnterburbia ' to occur...